Threats associated with build, operate and transfer (B.O.T) infrastructure projects in Southern Africa and the impact it has on the risk profile. - Moloigaswe, Shimah. (My University, 2014)
The rapid economic growth in many developing countries results in a high demand for infrastructure and governments find that they are unable to fund the vital infrastructure or to maintain the existing ones (Gupta and Sravat, 1998). To remedy this they are increasingly opting for an alternative source of funding through the large international companies which have considerable credit standing for concession contracts such as Build Operate and Transfer (BOT) since those companies have a much larger capacity to fund the large scale projects than the recipient country. The objective of this research project is to provide a brief review of the South African experience with the utilisation of the BOT approach for infrastructure developments, examining the risks and the measures used to mitigate them. This is so as to draw lessons for policy makers on how to improve the use of this strategic instrument for infrastructure provision. The emphasis will be on overall risks associated with the scheme as well as the mitigating factors in light of the current social, political and economic context of the country and the region. Data was collected using the Delphi survey method and the study targeted individuals who were knowledgeable and experienced with the issues under investigation and from different sectors involved with execution of BOT infrastructure development projects in South Africa. These included contractors, lenders, operators as well as some from the host government. The questionnaire was designed to identify the perceptions of the individuals regarding risk management in BOT projects as well as identify significant risk associated with the scheme. The 10 most critical risks were ranked based on the ratings of the respondents in the final phase of the Delphi survey. The risk that was rated the most critical turned out to be ‘Political instability in the host country’. This is defined as the danger of political or financial instability in the host country caused by events such as insurrections, strikes, creeping expropriation and outright nationalization.
Keywords: Infrastructure (Economics); Risk assessment; Delphi method; Risk management